PENGETAHUAN, SIKAP, DAN DUKUNGAN KELUARGA MENGENAI SKRINING HIPOTIROIDISME KONGENITAL PADA IBU HAMIL TRIMESTER KETIGA DI PUSKESMAS UJANMAS - Ekadewi Retnosari; Kustinah Kustinah; Rosyati Pastuty; Rita Kamalia (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2025)
Congenital hypothyroidism (CH) is a critical endocrine disorder that occurs when a newborn's thyroid gland fails to produce adequate thyroid hormones, leading to potential developmental and intellectual disabilities if left untreated. Early detection through neonatal screening programs is essential for preventing these adverse outcomes and ensuring timely intervention. This study investigated the knowledge, family support, and attitudes of pregnant women regarding congenital hypothyroidism (CH) screening at the Ujanmas Health Center in 2024. The research employed a cross-sectional design with accidental sampling, involving 33 respondents. The research subjects are third-trimester pregnant women who meet the inclusion and exclusion criteria. This study uses the Spearman rank correlation test with an alpha of 0.05. The findings indicated that 42.4% of the respondents had poor knowledge of CH screening, while 24.2% had good knowledge. A significant positive correlation was found between knowledge and attitudes (P = 0.005, CC = 0.475), and between family support and attitudes (P = 0.034, CC = 0.371). The study concluded that enhancing knowledge through targeted educational programs and increasing family support are crucial for fostering positive attitudes and higher participation rates in CH screening programs.